The unmet needs for family planning and its associated factors among ever married women in selected villages of Anekal taluk, Karnataka: a community based cross sectional study - George, Neethu; T., Sulekha; Ramachandran, Adithya; Peters, Andrean; Kiran, Pretesh Rohan (International Journal Of Community Medicine And Public Health, 2018)
Background: According to the United Nations, India will become the most populated country by 2050.This will lead to further strain in social and economic life. Family planning plays a major role in bridging this rapid population growth. But unmet needs for family planning prevent women from availing this benefit. Aims of the study were to determine the prevalence of unmet needs for family planning and its associated factors among ever married women in selected villages of Anekal taluk, Karnataka. Methods: This was a cross sectional study conducted during a period of two months among ever married women in selected villages of Anekal. A structured interview schedule consisting of questions about unmet needs for family planning and its determinants was administered to 133 ever married women. Results: Of the 133 study participants 127 (95.5%) were aware of at least one contraceptive method. The prevalence of unmet needs for family planning was 11.3%. Younger age (18-24 years), <5 years active years of married life, women having a single live child and who were a sole decision maker had higher unmet needs for family planning. Among the women who had unmet needs for family planning, the major reason reported was family and cultural problems. Conclusions: The unmet need for family planning was found to be 11.3% which is more than the state value of 8.8% (rural Karnataka NFHS 4). So there is a need to create increased awareness among the women in the study area regarding the importance of contraceptive measures in the family and the society.